Antara organisasi dan akademik: Dinamika performa mahasiswa - Rohmahwati, Desy; Hutahaean, Erik Saut H; Muzzamil, Ferdy (Jurnal Psikologi Poseidon, 2025)
This study examines the relationship between organizational role conflict and academic performance among university students. This research uses a quantitative approach with correlational methods to analyze data collected from 111 active student respondents who participate in organizations. Organizational role conflict arises when students prioritize organizational responsibilities over academic tasks, leading to stress and decreased academic performance. The study identifies various factors contributing to role conflict, including time management issues, stress from organizational duties, and negative identification processes. The research highlights the impact of role conflict on academic performance, such as delayed task completion, reduced academic motivation, and lower grades. The findings suggest that effective time management, clear role expectations, and support systems are crucial for students to balance organizational and academic responsibilities. The study provides insights into the challenges faced by students in managing dual roles and offers recommendations for improving academic performance through better role management.